The Star-Touched Queen - Chokshi, Roshani (New York : St. Martin's Griffin, 2016)
Scorned and feared because of a formidable horoscope, Maya commits herself to her education only to land in an arranged marriage that culminates in her sudden elevation to the throne, a situation threatened by dark secrets and magic.
Keywords: Fantasy; Marriage -- Fiction; Fate and fatalism -- Fiction; Magic -- Fiction; Prophecies -- Fiction; Arranged marriage -- Fiction; Fate and fatalism -- Fiction; Magic -- Fiction; Prophecies -- Fiction; Fantasy fiction